Utilization of Edlink Application by Lecturers in the Learning Process at Citra Bangsa University - Atama, Joan Corlince; Sogen, Maria Magdalena Beatrice; Saekoko, Jurni; Keling, Rijkar Putra.S; Neonbasu, Didimus Armindo (JUPE : Jurnal Pendidikan Mandala, 2025)
The development of information technology has encouraged the transformation of higner education systems, one of which is through the utilization of Learning Management System (LMS) applications such ad EdLink. This study aims to analyze the utilization of the EdLink application by lecturers in the laerning process at Citra Bangsa University. The problem raised in the field, such as tecnical obstacles and the need for training. Perkembangan teknologi informasi telah mendorong tranformasi sistem pendidikan tinggi, salah satunya melalui pemanfaatan aplikasi Learning Management System (LMS) seperti EdLink. Penelitian ini bertujuan untuk menganalisis pemenfaatan aplikasi EdLink oleh dosen dalam proses pembelajaran di Universitas Citra Bangsa. Permasalahan yang diangkat adalah kesenjangan antara harapan optimalisasi pembelajaran daring dengan kenyataan dilapangan, seperti kendala teknis dan kebutuhan peneliti